We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+2
165
2
avatar

Find the non-zero value of c  for which there is exactly one positive value of  b for which there is one solution to the equation \(x^2 + \left(b + \frac 1b\right)x + c = 0\)

 Jun 1, 2019
edited by Guest  Jun 1, 2019
 #1
avatar+8829 
+2

There is only one solution for  x  when the discrimant is  0 , that is, when...

 

\((b+\frac1b)^2-4(1)(c)\ =\ 0\\~\\ (b+\frac1b)^2-4c\ =\ 0\\~\\ (b+\frac1b)(b+\frac1b)-4c\ =\ 0\\~\\ b^2+2+\frac{1}{b^2}-4c\ =\ 0\\~\\ b^2+(2-4c)+\frac{1}{b^2}\ =\ 0\\~\\ b^4+(2-4c)b^2+1\ =\ 0\qquad\text{Let}\qquad u=b^2\\~\\ u^2+(2-4c)u+1\ =\ 0\)

 

There is only one solution for  u, and thus only one positive value of  b ,  when...

 

\((2-4c)^2-4\ =\ 0\\~\\ (2-4c)^2\ =\ 4\\~\\ 2-4c\ =\ 2\qquad\text{or}\qquad2-4c\ =\ -2\\~\\ c\ =\ 0\phantom{2-4}\qquad\text{or}\qquad c\ =\ 1\)

 

The non-zero value of  c  is  1 .

 

----------------------------------------

 

To check this answer, let's find the values of  b  for which   \(x^2+(b+\frac1b)x+1=0\)   has only one solution.

 

\(x^2+(b+\frac1b)x+1=0\)     has only one solution when....

 

\((b+\frac1b)^2-4\ =\ 0\\~\\ b^2-2+\frac{1}{b^2}\ =\ 0\\~\\ b^4-2b^2+1\ =\ 0\\~\\ (b^2-1)^2\ =\ 0\\~\\ b\ =\ \pm1\)

 

There is only one positive value of  b  for which there is one solution to the equation  \(x^2+(b+\frac1b)x+1=0\)

___

 Jun 1, 2019
 #2
avatar+7747 
0

The exact same question has been asked here before.

 

https://web2.0calc.com/questions/help_77926

 Jun 1, 2019

12 Online Users

avatar